Augmenting Digital Nature: Generative Art as a Constructive Feedback Loop. (7th April 2022) - Crespo, Sofia; McCormick, Feileacan
Abstract: Sofia Crespo and Feileacan McCormick use AI in their generative artworks. They are interested in natural ecology, biology and the way organisms adapt and evolve in relationship to their environment. The augmentation of their own creativity by AI helps them process complicated, unsolvable 'wicked' problems and produces some stunningly beautiful art along the way.